Can combining different risk interventions into a single formulation contribute to improved cardiovascular disease risk reduction? Rationale and design for an international, open-label program to assess the effectiveness of a single pill (amlodipine/atorvastatin) to attain recommended target levels for blood pressure and lipids (The JEWEL Program). - Hobbs, F; Gensini, G; Mancini, G; Manolis, A; Bauer, B; Böhler, S; Genest, J; Feldman, R; Harvey, P; Jenssen, T; Metcalfe, M; da Silva, P (2006)
BACKGROUND: In order to prevent cardiovascular events, it is essential to effectively manage overall risk of cardiovascular disease. However, despite guideline recommendations to this effect, current management of the major, modifiable cardiovascular risk factors such as hypertension and dyslipidemia is disconnected and patient adherence to therapy is poor. This is particularly important for patients with multiple cardiovascular risk factors, who are often prescribed multiple medications. The JEWEL study program will investigate the use of single-pill amlodipine/atorvastatin as a strategy to improve management of these patients. METHODS: The JEWEL program consists of two 16-week, international, open-label, multicenter, titration-to-goal studies in patients with hypertension and dyslipidemia. The 2 studies differ based on country of enrollment and certain tertiary endpoints, but the overall designs are very similar. Patients have been enrolled from 255 centers across Canada and 13 European countries. The study is designed to assess the efficacy, safety, and utility of amlodipine/atorvastatin single-pill therapy in a real-world setting. Patients will be initiated at a dose of amlodipine 5 mg/atorvastatin 10 mg, unless previously treated, and will be uptitrated as necessary. The primary efficacy parameter is the percentage of patients, at different levels of cardiovascular risk, achieving country-specific guideline-recommended target levels for blood pressure and lipids. A secondary analysis of efficacy measured attainment of the same single goal for blood pressure across all study participants (JEWEL I and II) and the same single goal for LDL-C across all study participants (JEWEL I and II). The program will utilize a newly developed questionnaire to gain better understanding of participants' beliefs and behaviors towards medical treatment of their multiple risk factors. Approximately 2850 patients will be enrolled in the program, which is due to be completed in August 2005. CONCLUSION: The JEWEL program will assess the effectiveness of a single pill (amlodipine/atorvastatin) in targeting the two principal risk factors for cardiovascular disease simultaneously to achieve nationally applicable treatment targets in a routine clinical practice setting.